Network of International Cooperative Learning Educators and Enthusiasts (NICLEE): Cultivating Global Connections - Arató, Ferenc; Davidson, Neil; Stevahn, Laurie; Sharan, Yael (Autonomy and Responsibility Journal of Educational Sciences, 2023)
Desmond Tutu speaks to the fundamental truth that the human species relies on cooperation for its survival. While we may see ourselves as individuals, the reality is that we are all interconnected and our fates are intertwined. This is especially true when it comes to learning and education. We cannot learn in isolation; we need teachers, mentors, peers, and a community that supports us. The act of learning itself is a cooperative process, where we share knowledge and ideas with others to construct deeper understanding. In short, the quote reminds us that we are not alone in this world, and that our success and happiness are tied to the success and happiness of others. It is only through cooperation and collaboration that we can achieve great things and create a better future for all.